Neonatal amygdala lesions advance pubertal timing in female rhesus macaques. (January 2015) - Stephens, Shannon B.Z.; Raper, Jessica; Bachevalier, Jocelyne; Wallen, Kim
Highlights: Neonatal amygdala lesions result in earlier menarche and first ovulation. Neonatal amygdala lesions do not decrease the length of the pubertal period. Greater body weight cannot account for the effects of earlier puberty onset. The effects of social rank on menarche in amygdala-lesioned females are unclear. Social rank did not alter the timing of first ovulation. Summary: Social context influences the timing of puberty in both humans and nonhuman primates, such as delayed first ovulation in low-ranking rhesus macaques, but the brain region(s) mediating the effects of social context on pubertal timing are unknown. The amygdala is important for responding to social information and thus, is a potential brain region mediating the effects of social context on pubertal timing. In this study, female rhesus macaques living in large, species-typical, social groups received bilateral neurotoxic amygdala lesions at one month of age and pubertal timing was examined beginning at 14 months of age. Pubertal timing was affected in neonatal amygdala-lesioned females (Neo-A), such that they experienced significantly earlier menarche and first ovulation than did control females (Neo-C). Duration between menarche and first ovulation did not differ between Neo-A and Neo-C females, indicating earlier first ovulation in Neo-A females was likely a consequence of earlier menarche. Social rank of Neo-A females was related to age at menarche, but not first ovulation, and social rank was not related to either event in Neo-C females. It is more likely that amygdalectomy affects pubertal timing through its modulation of GABA-ergic mechanisms rather than as a result of the removal of a social-contextual inhibition on pubertal timing.